DARI REKOMENDASI KE KONVERSI: PERAN STRATEGIS WOM DAN MEDIA SOSIAL DALAM PEMASARAN JASA KONSTRUKSI - Fatmawati, Fatmawati; Ismaliyanto, Junef (Management Research and Business Journal, 2025)
In the high-value and complex construction services industry, marketing strategies are not only aimed at reaching the market but also building client trust and loyalty. This study aims to analyze the influence of Word of Mouth (WOM) and social media on the effectiveness of marketing strategies in the construction services sector. This study uses a quantitative approach with a descriptive-causal design. The sample consisted of 97 respondents determined through purposive sampling, with criteria of at least five years of experience an involvement in marketing activities. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS. The results of the analysis indicate that WOM and social media have a positive and significant influence on the effectiveness of marketing strategies. The regression coefficients of each variable indicate that both provide a significant contribution to encouraging client engagement, building brand reputation, and increasing the success of construction service promotions. Overall, the regression model explained 55.7% of the variation in marketing strategy effectiveness, confirming the strategic role of integrating interpersonal and digital communication in this context. The novelty of this study lies in the simultaneous examination of two communication channels—WOM and social media—in the context of construction services marketing in Indonesia, a relatively understudied area. This research provides an empirical basis for companies to design more effective, adaptive, and customer-driven marketing strategies. This research is expected to serve as a foundation for developing communication strategies that are more responsive to digital dynamics and the needs of the professional services market.